Islamic Republic of Iran : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
In recent years, the IMF has released a growing number of reports and other documents covering economic and financial developments and trends in member countries. Each report, prepared by a staff team after discussions with government officials, is published at the option of the member country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet